Intraventricular haemorrhage in very preterm neonates - Kapoor, Saurabh; Sharma, Ravi; Sapare, Anil Kumar; Aggarwal, Rajiv (International Journal of Contemporary Pediatrics, 2018)
Background: The objective of the current study was to evaluate the incidence of intraventricular haemorrhage and its associated risk factors in preterm neonates. Methods: This cohort study done at Neonatal Intensive Care Unit of a tertiary care hospital in south India enrolled 104 preterm neonates with either gestational age <32weeks and/or birth weight <1500 grams at birth. These babies were serially screened for intraventricular haemorrhage by doing a neurosonogram on day3 and day 14 of life. Results: Incidence of IVH was found to be 18.2%. Amongst these cases 52.6% babies had Grade I, 36.8% babies had Grade II and 10.6% babies had Grade III intraventricular hemorrhage with ventriculomegaly, as per Papile grading system. It was seen that hypotension needing use of inotropes and neonatal sepsis were significantly associated with IVH. Conclusions: The incidence of IVH in babies born with gestational age <32weeks and/or birth weight <1500 grams was 18.2% in our study. Neonatal sepsis and hypotension requiring use of inotropes were found to be the significant risk factors in this population.